FA‘ĀLIYAH USLŪB JIGSAW LI TARQIYYAH QUDRAH AL-ṬULLĀB ‘ALA FAHM AL-NAḤW BI MA’HAD DĀR AL-IHSĀN ACEH BESAR - Falah, Moch. Fajarul; Husaini, Husaini; Raju, Mohd. Jaisar (Islam Futura, 2022)
Nahwu is one of the subjects of the Arabic language that is taught in schools under the auspices of Islamic institutes. The teacher used the book “Mutammimah Al-Ajrūmiyah” using the traditional methods at the Dar Al-Ihsan Institute, Aceh Besar. The researchers noticed that the teacher's teaching process did not consider the students' conditions, as they did not cooperate in the learning process, so the process of teaching and learning became boring for them. This condition affects their lack of understanding of the lesson. Therefore, this study aims to apply the cooperative learning method with the Jiqsaw method to improve the students' ability to understand the rules of grammar and identify the students' responses in the learning process and the teacher's efforts to overcome the problems that occur during the learning process. This research was conducted using the action research method in the classroom, and the research tools used were tests, questionnaires and observations. The research participants of this study are all students of the Dar Al Ihsan Institute, which numbered 518 students, while the sample taken is the fourth-grade students, numbering 27 students. As for the results of this research, the students' average score is 89.44, which indicates the effectiveness of this method in improving the students' ability to understand grammatical rules. The teacher overcomes the problem by discussing and using concept maps to make it easier for students to understand the lessons when learning and provide learning motivation so that they are happy when learning the language. Students' responses in the learning process are greatly improved.